AWARENESS TOWARDS ANTIMICROBIAL STEWARDSHIP AMONG UNDERGRADUATE MEDICAL STUDENTS - Dr. Razia Abdul Rasheed; Dr. Sridevi R; Dr. Vijayalakshmi S; Dr. Raja TAR ; Dr. Senthil G; Dr. Kalaiselvi B; Dr. Sudha K M; Dr. Brethis C.S (South Eastern European Journal of Public Health, 2025)
Background: Antibiotics are a valuable resource and their discovery has saved countless lives. The overwhelming and untenable use of antimicrobials (AM), contributes to the emergence of antimicrobial resistance (AMR). Against this background, WHO implemented Antimicrobial stewardship (AMS) - an initiative to refine the usage and prescribtion of antibiotics. The aim of this study is to analyze the awareness regarding AMS among undergraduate medical students. Methods: Following approval from IEC, a survey was conducted among 132 third-year MBBS students at Melmaruvathur Adhiparasakthi Institute of Medical Sciences and Research. Written informed consent was obtained. Pre-test assessment was done. Perception program on antimicrobial stewardship: A competency-based approach recommended by WHO was given to the study participants and the questionnaires regarding the same were used. Post-test response was documented. An overall assessment was done by comparing the scores obtained during pre-test and post-test. Frequency and proportions were determined with descriptive statistics. 25–75% interquartile ranges (IQR) of scores were compared using the non-parametric Mann–Whitney test. Results: 93 out of 132 students, completed both pre-test and post-test. The average score increased by 48.7% from pre-test to 73.7% post-test. Overall, most participants (56.9%) strongly agreed with the statement that ASP is mandatory in our hospital. Regarding the perception, at patients request, I would prescribe antibiotics - 41.9% of the participants strongly disagreed. There was a marked variability in IQR (2 to 3) corresponding to the fact, that Emergence of antimicrobial resistance is inevitable and ASP will help optimize treatment outcomes. Conclusion: The post-test scores of the participants showed a significant increase, demonstrating that knowledge was enhanced through the ASP sensitization program. Initial Steps can be taken in every academic year of the medical undergraduates, to participate in basic components of an antimicrobial stewardship program